Your place or mine? The love hotel as a post-domestic hyperreality - Pienaar, Alex (School of Architecture, Planning and Geomatics, 2024)
“Your Place or Mine? The Love Hotel as a Post-Domestic Hyperreality” is a thesis project which explores themes of pleasure, intimacy and domesticity; as well as its antithesis, postdomesticity; within the city of Cape Town. The foundation upon which my research is based is an inquiry into queer and feminist theory, but the end-goal of the project is to create a proposal which can be relatable and accessible across gender and sexual boundaries, spanning various scales including the body, architectural and non-architectural space(such as the space occupied or inferred though bodily movement), the city and beyond. “The Love Hotel”, is an imagined building which accommodates a multitude of programmes centered around spatio-relational aspects of pleasure and intimacy in our post-modern context. The exact parameters of this architecture will be defined over the course of this paper. In Part 1, I will begin my inquiry with a background study on queer phenomenology in architecture, introducing the concept of Drag Architecture. I will follow this with a look at Closeting in terms of the queer experience and architectural manifestations of this concept, introducing the Boudoir as an important spatial archetype. In Part 2, I will delve into the intricacies of Domesticity, tracing its history from the 19th century, as well as the profound impact it had on gender and sexual relations of the next two centuries. The influence of commercial products and technology for the home as well as an introduction to the important theme of Post-Domesticity will also be discussed. This will follow with a comparative case-study of three important modernist queer homes; St Anne's Court by Raymond McGrath, E.1027 by Eileen Gray and The Glass House by Philip Johnson to explore possible alternative models for a new post-domestic space. In Part 3, I will explore themes of sexuality and pleasure in a more urban setting. I will briefly return to the 19th century to discuss the influence of domesticity on urban planning, comparing the practice of the Flâneur to the gay practice of Cruising. Next, I will use Bradley Rink's analysis of De Waterkant In Cape Town; “Village People”, as a spring board to discuss the commercialisation of sexuality and its dilution in the urban practice of Quartering, followed by a discussion of these themes in the design of the Erotisch Centrum in Amsterdam, by Moke Architecten. At this point, the reader would be fully-equipped for an analysis of the Love Hotel, a Japanese building typology of sex hotel; and the Fun Palace, a design by Cedric Price, which explores some of its ideas in a less overtly-sexual format. The final section of this paper, Part 4, will outline a site of investigation for my own reinterpretation of the Love Hotel on an historical site in Cape Town's City Center. In this section, I will explore the history of the site, as well as the intricacies of preserving the existing building's historical ‘skin 'through the Façade Retention Method. Rebuking this method as potentially insensitive, I will then explore different approaches to architectural ‘skin' in some technical case studies. I will conclude with a brief overview of the topics discussed in this paper and lay out my plans for the next section of my thesis and how I will approach designing the new Love Hotel.